Study and Simulation of Transporting Radio Frequency Signals over Free Space Optics for Achieving High Data Rate and Power Saving - Aameer Ibrahim, Isam; Safa’a Mansour, Tahreer (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The remarkable technology for seamless integration of wireless and optical networks is radio frequency signals over Free Space Optics (FSO). This research study and simulation examine the design and evaluation performance of Radio Frequency over FSO (RF-FSO) wireless communication technology. These systems are implemented through medium communication link ranges to overcome excessive sensitivity of atmosphere medium and meet the requirements of a wide variety of optical wireless applications. There are two ways to achieve the application of the design mentioned above. The first way is the application of the  Three modulation schemes of technology that is Amplitude shift keying (ASK), Quadrature amplitude modulation (QAM), and Quadrature phase-shift keying (QPSK) of digital modulation. The design of these modulation schemes is realized by using optiwave software to study the transmission of RF signals over the FSO channel and compare the three modulation techniques into the RF-FSO system. RF signals with the frequency range from (20 to 60) GHz is used in RF-FSO system and many carrier optical signals where the higher RF has a wider bandwidth to carrying larger information. To increase the transmission of data rates Wavelength Division Multiplexing (WDM) technology is used. The second way is based on a mathematical model which has been proposed for this study. This mathematical model calculates optimal beacon period (BI), and optimal listen interval (LI) to preventing the overlapping of time between the signals and the decrease in the required power. Using different weather conditions samples, the simulation results revealed that the best performance of the RF-FSO system is from link range, and the receiver is more sensitive. The simulation results are as follows: Two independent channels are transmitted 20 Gbps over ranges from (263 m to 6.55 km), while four channels are transmitted 40 Gbps over ranges from (257 m to 5.95 km), and eight independent channels transmit 80 Gbps over distance from (203 m to 5.2 km)